ENHANCING LANGUAGE LEARNING THROUGH THE JIGSAW METHOD: INSIGHTS AND STRATEGIES - Tatyana Trigulova; Madinabonu Fayzullayeva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The Jigsaw method, a cooperative learning technique, has gained significant attention in the field of English Language Teaching (ELT) for its ability to foster active engagement, collaboration, and deeper understanding among students. This article explores the application of the Jigsaw method in ELT classrooms, highlighting its theoretical foundations, practical implementation, and empirical evidence of its efficacy. Through a review of relevant literature and case studies, the article provides insights into the benefits of the Jigsaw method in enhancing language proficiency, promoting critical thinking, and cultivating a positive learning environment. Detailed examples and recommendations are presented to guide ELT practitioners in effectively integrating the Jigsaw method into their instructional practices.